Estudo da mortalidade associado ao transtorno de abuso e dependência ao álcool - Silva, Jailson Vilberto de Sousa (2017)
Introduction: Alcohol abuse is considered a public health problem in the world and in Brazil. It accounts for 5.9% of the world's deaths according to the World Health Organization (OMS). In addition to health damage, studies in Brazil found the risk of death in men around 10 times higher than in women, with a high prevalence in the Northeast. In the years 2003 to 2007, a high prevalence was observed related to alcohol abuse in men, with higher frequency in the 4th and 5th decades of deaths recorded by the Death Verification Service (SVO / PB). Objective: To verify the association of mortality due to mortis related to the disorder of alcohol abuse and dependence in deaths admitted to the SVO / PB in the year 2015. Methods: Cross-sectional, quantitative study. The sample consisted of deaths in the year 2015 that, by criterion, were entered in the SVO / PB, in males, aged between 20 and 50 years. The data were collected from the death certificates and the admission forms. Statistical analyzes were performed in the SPSS® and R® programs to evaluate the association between the variables and Pearson's Chi-square test, Fisher's exact test, logistic regression with p <0.05 and as association measure was calculated The prevalence ratio with Confidence Interval (CI). Results: There were 972 deaths in men in the year 2015 in Paraíba. In the age group of 20 to 50 years, 192 deaths were verified and of these 28%, which corresponds to 54 cases, had a death related to alcohol abuse. In the sociodemographic analysis, the highest prevalence was found in the group of deaths due to alcohol abuse for the age group of 40 to 50 years old in a percentage of 66.7%, the brown ethnicity found was 98.1% of the cases, the low level of schooling Accounted for 70.4% of cases, single marital status appeared in 83.3% of cases. Regarding the medical history reported by the family, the most frequent clinical signs were from chronic diseases, with 52.2% of the occurrences being the most frequent: limb edema with 26% and malnutrition 26%; Mental disorders accounted for 42.77% of the signs reported, being the most frequent were: smoking with 34% and alcoholic epilepsy with 22%. The majority of deaths in the alcoholic group occurred in hospitals and health facilities with 44.4% of occurrence. The proportion of deaths in alcoholics with associated digestive tract causes was 55.6%, with 30 cases and the prevalence rate of this association was 9.53 with Confidence Interval - IC 4.58 - 20.60. The highest frequency of deaths was in João Pessoa, where the SVO / PB is located, it was observed that there was statistical significance for the difference between the groups that received assistance by city and in the association between the group that died in hospitals and services Health by city, the highest proportion in the city of João Pessoa in both cases, 44.8% and 33.3%, respectively. Conclusion: To investigate the epidemiological aspects of the deaths through clinical necropsy, it reinforces the importance of information systems for the planning, evaluation and execution of health actions, assisting in the policy of harm reduction through alcohol abuse.